Face mask use and physical distancing before and after mandatory masking: Evidence from public waiting lines - Gyula Seres; Anna Balleyer; Nicola Cerutti; Jana Friedrichsen; Müge Süer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
During the COVID-19 pandemic, the introduction of mandatory face mask usage was accompanied by a heated debate. It was argued that community use of masks creates a false sense of security that could decrease social distancing, thus making matters worse. We conducted a randomized field experiment in Berlin, Germany, to investigate whether masks lead to decreases in distancing and whether this mask effect interacts with the introduction of a mask mandate in Berlin. Joining lines in front of stores, we measured the distance kept from the experimenter in two treatment conditions - the experimenter wore a mask in one and no face covering in the other - both before and after the introduction of mandatory mask use in stores. We find no evidence that mandatory masking has a negative effect on distance keeping. To the contrary, in our study, masks significantly increase distancing and the effect does not differ between the two periods. Further, we find no evidence that the mask mandate affected distancing. However, our results suggest that the relaxation of shop opening restrictions had a negative effect on distancing.
Keywords: I12; D9; C93; 330; COVID-19; Face Masks; Social Distancing; Risk Compensation; Field Experiment; Health Policy